Social differences between the general population and tuberculosis patients in Slovakia - Vyšehradský, Peter; Solovič, Ivan; Kotúľová, Lucia; Grendár, Marián; Rákošová, Monika; Hudečková, Henrieta; Vyšehradský, Robert (Frontiers in public health, 2025)
Point out the social specifics of patients with tuberculosis, which persist despite the socioeconomic development of Slovak society. A questionnaire survey was conducted on a sample of consecutive patients with newly diagnosed tuberculosis during the first half of 2023. The collected data were aggregated and compared with the results of European Health Interview Survey (EHIS) in 2019. We found significant differences in the distribution of the level of education, labour status, nutritional and marital status, financial poverty, smoking habits, alcohol consumption and number of rooms in the dwelling between the general population and TB patients in Slovakia. Moreover, a significant trend in the proportions was observed across contingency table categories for all ordinal variables with more than two levels. There are several significant social differences between patients with tuberculosis and the general Slovak population.